The effect of implementing information systems on MS Glow - Khotibul Umam (International Journal of Science, Engineering, and Information Technology, 2021)
Ms Glow is a company engaged in the beauty sector. Ms Glow is a local brand that presents a series of skincare, especially for Indonesian women, which was founded in 2013. Technology is growing very fast as is online sales. This Ms Glow Information System was designed to serve as a promotional medium for Ms Glow and to simplify the online buying and selling transaction process. The design of promotional media also considers the factors that can affect the target market and target audience, so that the desires of potential customers can be identified. The website created can display complete and clear information and contain transaction reports, which sometimes errors occur when processing data. Ms Glow's Information System is a website that makes it easy for shop owners and consumers to make sales transactions, purchase goods and report data. Using easy-to-read fonts, attractive photo images, and choosing the right color. This system is created using the PHP programming language with the MySQL database for data storage. The result of this system is that it can process product information, such as: managing user data, category data, goods data, and the process of purchasing goods transactions. Through this website, it is hoped that Ms Glow as previously mentioned can be implemented and improved